Pelaksanaan Program Penanaman Tanaman Obat Keluarga dalam Rangka Pemberdayaan Masyarakat Desa Tegal Kertha - Dyo, Dyo Wahyu Saputra; Putu Sariani, Ni Luh (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The Family Medicinal Plants (TOGA) planting program at SD 26 Pemecutan was implemented as part of a community service activity aimed at improving students’ health literacy and environmental awareness through participatory learning. This program was motivated by the underutilization of school land as an educational medium and the limited understanding of students regarding the benefits of traditional medicinal plants. The implementation methods included observation, coordination with the school, educational socialization, direct planting practices, and mentoring in plant maintenance. Students actively participated in all stages of the activity, from preparing planting media to caring for the plants. The types of plants cultivated included ginger, turmeric, galangal, and lemongrass, which are easy to grow and beneficial for health. The results showed increased student participation, improved knowledge about medicinal plants, and the creation of a greener and more educational school environment. The program also fostered responsibility and environmental care among students. Therefore, TOGA planting can serve as an effective educational approach in strengthening health education and environmental awareness from an early age.